2002
DOI: 10.1016/s1525-1578(10)60703-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Validation of the Modified Vienna Classification of Colorectal Tumors

Abstract: Although the Vienna classification has been introduced to resolve discrepancies in histological diagnoses of colorectal tumors between Western and Japanese pathologists, practical applications of this classification scheme have been problematic because invasion of the lamina propria of tumor cells is often difficult to recognize. Therefore, the following refinements of the classification criteria are needed: category 3, low-grade adenoma/dysplasia; category 4, intramucosal borderline neoplasia; 4-a, high-grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…The TP53 gene is one of the most frequently mutated genes in human cancers 4, 5, 23, 24. Approximately half of all cancers have mutated TP53 4, 5.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The TP53 gene is one of the most frequently mutated genes in human cancers 4, 5, 23, 24. Approximately half of all cancers have mutated TP53 4, 5.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mutation of the TP53 gene is found in 60–80% of CRCs 4, 5, 7. Mutation of the TP53 gene is a representative event during the progression of CRC 4, 5, 23, 24. Recent studies have shown that mutation of TP53 is observed more frequently in LC than in RC 9, 25.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24] Samples were processed for 25-30 cycles, with each cycle consisting of 30 sec at 94°C, 1 min at 55-58°C and 2 min at 72°C, followed by a final 10 min extension at 72°C. For quantitative detection of the allelic imbalance at each locus, the size of the 2 alleles (q-value) in a heterozygous sample was determined by comparison with the 2 highest peaks in the normal sample as described previously.…”
Section: Analysis Of Allelic Imbalance On Cancer-related Chromosomal mentioning
confidence: 99%